Do Prosecutors Have The Authority To Realize The Restorative Justice? An Indonesian Case - Sasongko, Andy; Abdul Madjid; Yuliati; Fachrizal Afandi (Audito Comparative Law Journal (ACLJ), 2025)
This article explores the role of a prosecutor in realizing restorative justice in Indonesia. This research employs a socio-legal method, focusing on how legal certainty, legal order, justice, and truth can be achieved by upholding human values,  religious norms, politeness, and decency. The Attorney General of the Republic of Indonesia has established, among others, the prosecutorial function and authority to promote restorative justice in terminating prosecutions in Indonesia based on Prosecutor's Regulation of Indonesia (PERJA RI) Number 15 of 2020 concerning Termination of Prosecutions Based on Restorative Justice. With the amendment of PERJA RI, it is hoped that the public prosecutor in handling criminal cases will act more humanely and conscientiously, prioritizing restorative justice, which aims at restoration to protect the lives of victims and people who commit criminal acts on the grounds of humanity and justice in society instead of focusing on retaliation against perpetrators. As the state institution responsible for prosecutions, the prosecutor's office strives to uphold legal certainty, truth, and justice in line with legal principles while respecting humanity, morality, decency, and religious values.